The 7 Habits of Highly Effective People Training Development Model to Improve Elementary School Teachers' Competence - Helmy Bastian; Muslimin Ibrahim; Fifi Khoirul Fitriyah (Lembaran Ilmu Kependidikan, 2026)
Background - Enhancing elementary school teachers’ proficiency is crucial for improving the quality of basic education in Indonesia. However, developing an effective and sustainable training model that integrates character-based professional development, particularly through The 7 Habits of Highly Effective People framework, remains a significant challenge. Purpose - This study aims to examine the process of designing a training development model that supports the implementation of the 7 Habits framework in strengthening elementary school teachers’ competencies. Method/Approach - This study employed a literature review method. Data sources consisted of ten scholarly articles selected from an initial pool of 178 publications indexed in reputable international databases, including SpringerLink, Emerald Insight, Taylor & Francis Online, SAGE Journals, and ScienceDirect, published between 2020 and 2025. The selection process followed a multi-stage screening procedure, including identification, screening, and eligibility, based on predetermined inclusion and exclusion criteria. Findings - The findings reveal several key components that support effective training development: (1) systematic and structured program design, (2) integrative competency-based workshops, (3) sustained coaching and mentoring mechanisms, (4) professional learning community engagement, (5) technology-supported learning platforms, and (6) continuous evaluation and reflective practice. Balanced integration of these components is essential to promote meaningful habit formation and long-term professional development. Conclusions - An integrated and well-structured training model significantly contributes to strengthening teachers’ competencies and fostering sustainable professional habits. Institutional commitment and continuous support are critical factors in ensuring the effectiveness of such training programs. Novelty/Originality/Value - This study offers a conceptual framework for character-based teacher training development grounded in the 7 Habits approach, providing a holistic and adaptive model that integrates professional competence and personal habit formation. It contributes to the advancement of teacher professional development models in the context of contemporary educational transformation.